ANALISIS KONDISI SOSIAL EKONOMI ORANG TUA TERHADAP TINGKAT PENDIDIKAN ANAK DI KABUPATEN JEMBER - Mucharom, Neviyani (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2018)
Resource-quality showed the strong commitment of the government in its economic development program, the demands of society were more complex and competition tight, especially in the era of globalization and so that free trade, it needed good quality of human resources, one of effort to improve human resources were through education. This research was conducted in Jember regency, the method for sampling by purposive sampling technique. The data Analysis Technique used Multiple Linear Regression. Based on the calculation results of SPSS, found: 1). There was the influence of social-economic condition level of parents foward education level of children in Jember regency. 2). There was the influence of parents education level toward children education level in Jember regency. 3). There was the influence of parents income to the level of education of children in Jember regency. 4). There was the influence ownership toward the level education of children in Jember regency. 5). There was the influence of hause type the level toward of children education in Jember regency. Keywords: Socio-economic, education level, income, ownership Facilities / wealth, and type Dwelling